Activation of TWIST Transcription by Chromatin Remodeling Protein BRG1 Contributes to Liver Fibrosis in Mice - Dong, Wenhui; Kong, Ming; Zhu, Yuwen; Shao, Yang; Wu, Dongmei; Lu, Jun; Guo, Junli; Xu, Yong (Frontiers in Cell and Developmental Biology, 2020)
Liver fibrosis is complex pathophysiological process to which many different cell types contribute. Endothelial cells play versatile roles in the regulation of liver fibrosis. The underlying epigenetic mechanism is not fully appreciated. In the present study, we investigated the role of BRG1, a chromatin remodeling protein, in the modulation of endothelial cells in response to pro-fibrogenic stimuli in vitro and liver fibrosis in mice. We report that depletion of BRG1 by siRNA abrogated TGF-b or hypoxia induced down-regulation of endothelial marker genes and up-regulation of mesenchymal marker genes in cultured endothelial cells. Importantly, endothelial-specific BRG1 deletion attenuated CCl4 induced liver fibrosis. BRG1 knockdown in vitro or BRG1 knockout in vivo was accompanied by the down-regulation of TWIST, a key regulator of endothelial phenotype. Mechanistically, BRG1 interacted with and was recruited to the TWIST promoter by HIF-1a to activate TWIST transcription. BRG1 silencing rendered a more repressive chromatin structure surrounding the TWIST promoter likely contributing to TWIST down-regulation. Inhibition of HIF-1a activity dampened liver fibrosis in mice. Similarly, pharmaceutical inhibition of TWIST alleviated liver fibrosis in mice. In conclusion, our data suggest that epigenetic activation of TWIST by BRG1 contributes to the modulation of endothelial phenotype and liver fibrosis. Therefore, targeting the HIF1a-BRG1-TWIST axis may yield novel therapeutic solutions to treat liver fibrosis.